Moderate hypothermia to treat perinatal asphyxial encephalopathy. - Azzopardi, D; Strohm, B; Edwards, A; Dyet, L; Halliday, H; Juszczak, E; Kapellou, O; Levene, M; Marlow, N; Porter, E; Thoresen, M; Whitelaw, A; et al. (Massachusetts Medical Society, 2009)
BACKGROUND: Whether hypothermic therapy improves neurodevelopmental outcomes in newborn infants with asphyxial encephalopathy is uncertain. METHODS: We performed a randomized trial of infants who were less than 6 hours of age and had a gestational age of at least 36 weeks and perinatal asphyxial encephalopathy. We compared intensive care plus cooling of the body to 33.5 degrees C for 72 hours and intensive care alone. The primary outcome was death or severe disability at 18 months of age. Prespecified secondary outcomes included 12 neurologic outcomes and 14 other adverse outcomes. RESULTS: Of 325 infants enrolled, 163 underwent intensive care with cooling, and 162 underwent intensive care alone. In the cooled group, 42 infants died and 32 survived but had severe neurodevelopmental disability, whereas in the noncooled group, 44 infants died and 42 had severe disability (relative risk for either outcome, 0.86; 95% confidence interval [CI], 0.68 to 1.07; P=0.17). Infants in the cooled group had an increased rate of survival without neurologic abnormality (relative risk, 1.57; 95% CI, 1.16 to 2.12; P=0.003). Among survivors, cooling resulted in reduced risks of cerebral palsy (relative risk, 0.67; 95% CI, 0.47 to 0.96; P=0.03) and improved scores on the Mental Developmental Index and Psychomotor Developmental Index of the Bayley Scales of Infant Development II (P=0.03 for each) and the Gross Motor Function Classification System (P=0.01). Improvements in other neurologic outcomes in the cooled group were not significant. Adverse events were mostly minor and not associated with cooling. CONCLUSIONS: Induction of moderate hypothermia for 72 hours in infants who had perinatal asphyxia did not significantly reduce the combined rate of death or severe disability but resulted in improved neurologic outcomes in survivors. (Current Controlled Trials number, ISRCTN89547571.)